# Length of Median of Triangle

Jump to navigation
Jump to search

## Contents

## Theorem

Let $\triangle ABC$ be a triangle.

Let $CD$ be the median of $\triangle ABC$ which bisects $AB$.

The length $m_c$ of $CD$ is given by:

- ${m_c}^2 = \dfrac {a^2 + b^2} 2 - \dfrac {c^2} 4$

## Proof 1

\(\displaystyle a^2 \cdot AD + b^2 \cdot DB\) | \(=\) | \(\displaystyle CD^2 \cdot c + AD \cdot DB \cdot c\) | Stewart's Theorem | ||||||||||

\(\displaystyle \leadsto \ \ \) | \(\displaystyle a^2 \frac c 2 + b^2 \frac c 2\) | \(=\) | \(\displaystyle {m_c}^2 \cdot c + \left({\frac c 2}\right)^2 c\) | substituting $AD = DB = \dfrac c 2$ and $CD = m_c$ | |||||||||

\(\displaystyle \leadsto \ \ \) | \(\displaystyle \frac c 2 \left({a^2 + b^2}\right)\) | \(=\) | \(\displaystyle m_c^2 \cdot c + \frac {c^2} 4 \cdot c\) | ||||||||||

\(\displaystyle \leadsto \ \ \) | \(\displaystyle \frac {a^2 + b^2} 2\) | \(=\) | \(\displaystyle m_c^2 + \frac {c^2} 4\) | ||||||||||

\(\displaystyle \leadsto \ \ \) | \(\displaystyle {m_c}^2\) | \(=\) | \(\displaystyle \frac {a^2 + b^2} 2 - \frac {c^2} 4\) | after algebra |

$\blacksquare$

## Proof 2

Let $\triangle ABC$ be embedded in the complex plane.

Let $A = \tuple {x_1, y_1}$, $B = \tuple {x_2, y_2}$ and $C = \tuple {x_3, y_3}$ be represented by the complex numbers $z_1$, $z_2$ and $z_3$ respectively.

Then:

\(\displaystyle AC\) | \(=\) | \(\displaystyle z_3 - z_1\) | |||||||||||

\(\displaystyle BC\) | \(=\) | \(\displaystyle z_3 - z_2\) | |||||||||||

\(\displaystyle AB\) | \(=\) | \(\displaystyle z_2 - z_1\) | |||||||||||

\(\displaystyle AD\) | \(=\) | \(\displaystyle \dfrac {AB} 2\) | |||||||||||

\(\displaystyle \) | \(=\) | \(\displaystyle \paren {\dfrac {z_2 - z_1} 2}\) |

Then:

\(\displaystyle AC + CD\) | \(=\) | \(\displaystyle AD\) | |||||||||||

\(\displaystyle \leadsto \ \ \) | \(\displaystyle CD\) | \(=\) | \(\displaystyle AD - AC\) | ||||||||||

\(\displaystyle \) | \(=\) | \(\displaystyle \paren {\dfrac {z_2 - z_1} 2} - \paren {z_3 - z_1}\) | |||||||||||

\(\displaystyle \) | \(=\) | \(\displaystyle \paren {\dfrac {z_1 - z_3} 2} + \paren {\dfrac {z_2 - z_3} 2}\) |

## Examples

### Triangle $\paren {1, -2}, \paren {-3, 4}, \paren {2, 2}$

Consider the triangle $\triangle ABC$ whose vertices are:

- $A = \paren {1, -2}, B = \paren {-3, 4}, C = \paren {2, 2}$

The length of the median of $\triangle ABC$ which which bisects $AB$ is $\sqrt {10}$.